Constituting 'Problems' through Policies: A WPR Approach of Policies Governing Teenage Pregnancy in France. Issue 2 (15th April 2023) - Komai, Eléonore
Abstract : This article examines the construction of policy problems through the exploration of the theoretical space opened up by the 'What's the Problem Represented to be?' (WPR) approach developed by Bacchi (2009) . It proposes a critical analysis of current policies governing teenage pregnancy in France through the deconstruction of the structures that have participated in shaping the 'problem' today. Focusing on discursive practices, the analysis unveils the political essence of the knowledge that constitutes the problem of 'teen pregnancy', and points to the constant flux characterising it, which is captured and stabilised in policymaking through problematisation. It is argued that these conclusions call for greater self-reflexivity in research and policymaking and prompt critical and feminist researchers to engage with disrupting current policymaking rationality.